Nitrogen fertilization on the leaf area index of two rice cultivars under upland conditions - Stone, Luis Fernando; Steinmetz, Sílvio (Pesquisa Agropecuaria Brasileira, 2014)
The effect of nitrogen fertilization on development of the Leaf Area Index (LAI) of the cultivars IAC 47 and CICA 4 was studied. Nitrogen increased the LAI in both cultivars due to its influence on the increment of the number of tillers and size of the leaves. The cultivar CICA 4 presented higher values of LAI due to its greater tillering capacity. Based on the Leaf Area Duration (LAD), CICA 4 showed a better response to the nitrogen fertilization (90 kg of N/ha) than IAC 47. The increment on LAD was 79% and 51,8% for the cultivars CICA 4 and IAC 47, respectively. This better response of LAD of cultivar CICA 4 reflected negatively in grain production due to occurrence of water deficiency. On the other hand, the leaf area developed by cultivar IAC 47 seems to have been adequate thereby contributing for the increase in production.